(untitled) (EAAE Annual Conference Proceedings, 2019)
Recently, I left the educational process at the Faculty of architecture and was given the opportunity to work as an assistant at the studio classes (so-called atelier). As a fresh graduate, I entered the teaching process with the student’s insight, but gradually I was confronted with the situation on the ‘other side’. The position of the fresh graduate has many advantages. For example, still up-to-date insight into the bureaucratic system of the faculty — with other words, knowing how it goes. On the other hand, one encounters questions: how to teach properly? In the present days a new field of study is still forming at the faculty: Landscape architecture, which was previously brought into the curriculum in the form of a module focused on garden and landscape architecture. There is room for some possible changes. At the faculty, questions also are arising on what the ideal composition of subjects of this newly shaped field should be, how much it has to do with architecture and how it is projecting in the environment disciplines.